IMPLEMENTASI PERATURAN PEMERINTAH NO 46 TAHUN 2013 PADA LAPORAN KEUANGAN WAJIB PAJAK BADAN DI MATARAM - Henny - Henny (InFestasi, 2016)
This study aims to explain how the implementation of Government Regulation No. 46 Year 2013Financial Report Corporate Taxpayers, especially UMKM in Mataram. This research is a case study.Informants consisted of tax authorities, Tax Consultants and the taxpayer. Data analysis was carriedout with reference to the cross-case analysis. The method used is a qualitative method.The conclusion of this study show that the presence of PP 46 of 2013 Financial Statements taxpayer makesa real case. This is because the size of the net income of a person or business entity will not affect theamount of tax to be paid, because the tax rate is calculated by multiplying directly against gross income, sothat the taxpayer does not have the opportunity to manipulate their tax payable. This will happen if thecounterparty of the taxpayer to report transaction activity that occurred or a company that had a turnovertaxpayer NPWP thus automatically tracked or known exactly amount. But if the counterparty of thetaxpayer is a small company that does not have a NPWP or have a NPWP, but do not obey the reportingof the transaction, it makes the taxpayer makes financial statements that do not correspond to the reality.That is to decrease the amount of profit, they set the gross turnover / turnover, cost of goods sold andexpenses incurred in the Profit / Loss them, so it will automatically shrink the number of tax payments.The suggestion from this study is that the set of rules or policies that make government may have data onthe amount of circulation of business taxpayers can use to minimize the chances of non complianceTaxpayers do with manipulating the Financial Statements. The suggestion from this study is that the set ofrules or policies that make government may have data on the amount of circulation of businesstaxpayers and counterparties that can be used tominimize non-compliance is opportunity for the taxpayer to manipulate the financial statements.